2015
DOI: 10.1111/ejh.12586
|View full text |Cite
|
Sign up to set email alerts
|

Vincristine efficacy and safety in treating immune thrombocytopenia: a retrospective study of 35 patients

Abstract: Although vincristine (VCR) is sometimes prescribed for newly diagnosed immune thrombocytopenia (ITP), its efficacy in refractory ITP and sustained efficacy has yet to be demonstrated. We describe our clinical experience and recommend vincristine's correct place in ITP management. This retrospective study analysed data from 35 patients with newly diagnosed (ND), persistent (P) or chronic (C) ITP treated with VCR. The initial response rate, defined as >30 × 10(9) platelets/L, reached 86% after a median of 7 [int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 24 publications
1
26
0
2
Order By: Relevance
“…It has been shown that platelet transfusions in this situation could lead to the cessation of bleeding without any serious effects (Salama et al, 2008). Vinca alkaloids (vincristine or vinblastine) could be added in case of severe bleeding but with risk of peripheral neuropathy especially in older patients (Stirnemann et al, 2016). We prefer to use vinblastine (5 mg/m 2 intravenously, not more than 8 mg) rather than vincristine because it is better tolerated in our experience.…”
Section: Nomentioning
confidence: 94%
“…It has been shown that platelet transfusions in this situation could lead to the cessation of bleeding without any serious effects (Salama et al, 2008). Vinca alkaloids (vincristine or vinblastine) could be added in case of severe bleeding but with risk of peripheral neuropathy especially in older patients (Stirnemann et al, 2016). We prefer to use vinblastine (5 mg/m 2 intravenously, not more than 8 mg) rather than vincristine because it is better tolerated in our experience.…”
Section: Nomentioning
confidence: 94%
“…Evidence for vinca alkaloids (VAs) is drawn mostly from studies conducted in the 1970s and 1980s, with few reports from the modern era. [48][49][50][51][52][53][54][55][56][57] Published studies vary in which VAs were used (vincristine vs vinblastine), the dose and number of infusions, use of maintenance dosing, and definition of response. Although initial reports were promising, relatively poor durability of response has dampened enthusiasm for VAs.…”
Section: Tiermentioning
confidence: 99%
“…However, later studies found that most responses were transient. [48][49][50][51]53 In a prospective trial, 35% of patients treated with vincristine achieved a platelet count .100 3 10 9 /L, but a 40% decline in the platelet count was observed as soon as 8 weeks after completion of 3 infusions. 51 The fleetingness of response to VAs must be balanced against their toxicities, which include vesication, constipation, and peripheral neuropathy (symptoms generally arise after cumulative vincristine doses of 30 to 50 mg).…”
Section: Tiermentioning
confidence: 99%
“…Studies that included more than 10 patients are reported in Table 3 [62][63][64][65][66]. The efficacy of vinca-alkaloids seems to be higher in newly diagnosed ITP than in persistent and chronic ITP.…”
Section: Vinca-alkaloids: Vincristine Vinblastinementioning
confidence: 99%
“…However, refractory ITP patients could benefit from vinca-alkaloids [67]. Usually, vincristine is used at a dosage of 1 mg/week, no longer than 4 weeks [65]. Vinca alkaloid effect is only suspensive with a sustained response of 37% and 20% at 1 and 2 years, respectively [65].…”
Section: Vinca-alkaloids: Vincristine Vinblastinementioning
confidence: 99%